CXCL5 activates CXCR2 in nociceptive sensory neurons to drive joint pain and inflammation in experimental gouty arthritis - Yin, Chengyu; Liu, Boyu; Dong, Zishan; Shi, Sai; Peng, Chenxing; Pan, Yushuang; Bi, Xiaochen; Nie, Huimin; Zhang, Yunwen; Tai, Yan; Hu, Qimiao; Wang, Xuan; et al. (Nature communications, 2024)
Gouty arthritis evokes joint pain and inflammation. Mechanisms driving gout pain and inflammation remain incompletely understood. Here we show that CXCL5 activates CXCR2 expressed on nociceptive sensory neurons to drive gout pain and inflammation. CXCL5 expression was increased in ankle joints of gout arthritis model mice, whereas CXCR2 showed expression in joint-innervating sensory neurons. CXCL5 activates CXCR2 expressed on nociceptive sensory neurons to trigger TRPA1 activation, resulting in hyperexcitability and pain. Neuronal CXCR2 coordinates with neutrophilic CXCR2 to contribute to CXCL5-induced neutrophil chemotaxis via triggering CGRP- and substance P-mediated vasodilation and plasma extravasation. Neuronal Cxcr2 deletion ameliorates joint pain, neutrophil infiltration and gait impairment in model mice. We confirmed CXCR2 expression in human dorsal root ganglion neurons and CXCL5 level upregulation in serum from male patients with gouty arthritis. Our study demonstrates CXCL5-neuronal CXCR2-TRPA1 axis contributes to gouty arthritis pain, neutrophil influx and inflammation that expands our knowledge of immunomodulation capability of nociceptive sensory neurons. Here, the authors demonstrate that CXCL5 expression is increased in ankle joints of gouty arthritis model mice. CXCL5-neuronal CXCR2-TRPA1 axis contributes to gouty arthritis pain, neutrophil influx and joint inflammation.